2008
DOI: 10.1080/14767050802037647
|View full text |Cite
|
Sign up to set email alerts
|

Face and brow presentation: Independent risk factors

Abstract: Face/brow presentation was associated with several adverse pregnancy outcomes, although there was a favorable neonatal outcome. Independent risk factors for face/brow presentation were fetal malformations and polyhydramnios, but primiparity had a protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Reported perinatal mortality, corrected for non‐viable malformations and extreme prematurity, varies from 0.6% to 5%, and cesarean delivery has been reported in up to 67.1% of cases of face presentation . Except for mentum posterior cases, safe vaginal delivery is suggested to be accomplished, and a trial of labor with careful monitoring of fetal condition and progress is not contraindicated unless macrosomia or a small pelvis is identified.…”
Section: Discussionmentioning
confidence: 99%
“…Reported perinatal mortality, corrected for non‐viable malformations and extreme prematurity, varies from 0.6% to 5%, and cesarean delivery has been reported in up to 67.1% of cases of face presentation . Except for mentum posterior cases, safe vaginal delivery is suggested to be accomplished, and a trial of labor with careful monitoring of fetal condition and progress is not contraindicated unless macrosomia or a small pelvis is identified.…”
Section: Discussionmentioning
confidence: 99%
“…Additional complications include premature rupture of membranes, pre PROM, placental abruption, cesarean delivery, postpartum hemorrhage, fetal malpresentations and significant perinatal mortality. 7,8,9,10,11 A study revealed significantly higher incidence of birth weight >4000 gm in mild unexplained polyhydramnios group as compared to the explained polyhydramnios group (18.6% vs 8.6%) with (p value <0.05 which is statistically significant). 12 Another study documented that the idiopathic polyhydramnios was not associated with an increased incidence of established perinatal outcomes like preterm births, small for gestational age, low birth weight, low APGAR score after 5 minutes of neonatal life, admissions of babies into NICUs and perinatal deaths.…”
Section: Introductionmentioning
confidence: 94%
“…The frequency of deflexion is likely to be lower when the progression is normal. However, although brow and sinciput presentations are commonly reported to be rare events [13][14][15] , the true incidence may be underestimated. The digital examination has already been proven inaccurate for diagnosing fetal position [7,8,10,34,35] , and we expect it to be equally imprecise in assessing fetal attitude.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In the remaining 3 cases, the orbits oriented upward in a transverse view of the maternal abdomen as the hallmark of OP presentation [2,[4][5][6][7][8][9][10] , a variety of the vertex presentation that may obstruct labor but is compatible with spontaneous vaginal delivery in a substantial proportion of cases [11,12] . OP rotation may also occur with deflexed presentations, such as sinciput and brow, that are known to interfere to a greater extent with the descent of the fetal head [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%